Does the discovery of the mimivirus call into question attempts to define life?. (19th September 2018) - Love, Luca Gregory
Abstract: Despite biology being 'The study of living organisms' (Proffitt, 2017 ), there is no consensus between biologists on the definition of life (Bedau, 2010 ). Defining life has challenged and divided biologists and philosophers alike ever since Aristotle proposed the first definition. Emerging fields like synthetic biology and exobiology have rekindled attempts at establishing a definition of life for practical purposes. The question presents many challenges with each attempt thus far leading to unintended implications and strong counterexamples. It is an inherently multidisciplinary challenge with each approach giving wildly varying and often irreconcilable definitions. The given definitions of life are numerous with over 300 definitions published in books and journals. The unique characteristics of the mimivirus, discovered in 2003, and later giant viruses, rekindled the discussion in defining life, indicating other complications in a definition.